1996
DOI: 10.1152/jappl.1996.80.2.706
|View full text |Cite
|
Sign up to set email alerts
|

Breath isoprene: temporal changes in respiratory output after exposure to ozone

Abstract: Isoprene is a major hydrocarbon found in human breath. This study was conducted to evaluate whether respiratory isoprene output could serve as a monitor for ozone exposure. Healthy young adult subjects (n = 10) underwent chamber exposure on separate days to filtered air and to a variable concentration of ozone. Exposures had durations of 130 min that included alternate periods of rest and light treadmill exercise; breath was sampled pre- and postexposure. For six subjects, breath was resampled 19 +/- 1 h poste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
2
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 0 publications
1
39
2
2
Order By: Relevance
“…This may reflect different kinetics for damage to proteins and their appearance in the systemic circulation. In contrast to other workers who found increased breath isoprene in conditions associated with increased oxidative stress to lung epithelia the authors found decreased levels during acute respiratory exacerbation which increased towards normal, following treatment [20]. The ability to assess free radical damage/activity has always been compromised by limitations in the assays available.…”
Section: Markers Of Free Radical Damage and Total Cholesterolmentioning
confidence: 78%
“…This may reflect different kinetics for damage to proteins and their appearance in the systemic circulation. In contrast to other workers who found increased breath isoprene in conditions associated with increased oxidative stress to lung epithelia the authors found decreased levels during acute respiratory exacerbation which increased towards normal, following treatment [20]. The ability to assess free radical damage/activity has always been compromised by limitations in the assays available.…”
Section: Markers Of Free Radical Damage and Total Cholesterolmentioning
confidence: 78%
“…Other exhaled compounds have attracted attention in a medical context: Ethane and n-pentane were linked to the in vivo level of lipid peroxidation and oxidative stress [2][3][4], breath acetone was shown to correlate with the metabolic state of diabetic patients [5] or mice on a ketogenic diet [6], and a decrease in exhaled isoprene was reported shortly after ozone exposure [7] and in acute pulmonary exacerbations of cystic fibrosis (CF) [8]. Yet, despite a growing scientific focus on nitric oxide and other exhaled biomarkers of pulmonary disease [9,10], data on breath VOC remain scarce and important methodological questions unanswered, such as the standardised collection, handling and analysis of human breath samples.…”
mentioning
confidence: 99%
“…31 Increases in isoprene concentrations in the breath have been observed in states of acute tissue injury such as myocardial infarction and acute lung injury. 32,33 A recent study on gas chromatographic breath analysis of uremic rats showed an early increase of isoprene after induction of kidney injury. 34 In human beings, current data indicate an increase of isoprene in the breath during a hemodialysis session.…”
Section: In the Breathmentioning
confidence: 99%